PEMBANGUNAN TUGU MENGKARAS SEBAGAI PILAR HARMONI DAN KEMAJUAN BAGI GENERASI DESA KERAKAS KECAMATAN SUNGAISELAN MENGKARAS - Zetira, Zetira Rizqia Erlin; Saputra, Nanda; Melinda, Melinda; Rosmawati, Rosmawati; Pratiwi, Saskia; Indriani, Berlian; Astuti, Meti; Akbar, Alif Yafi; Bil Haki, Arif; Sanjani, Fenti; Lathiifah, Iis Juniati (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
The construction of the Mengkaras Monument in Kerakas Village is a strategic effort to strengthen the village's identity while enhancing social harmony and community pride. As a village monument, its presence is expected to serve as a symbol representing the local character and history, while also beautifying the surroundings. The community service efforts in building the Mengkaras Monument were carried out through a participatory approach, involving various elements of society, including village leaders, youth, and social groups. Research findings indicate that the Mengkaras Monument plays a role in fostering a sense of belonging among residents, serving as a hub for social activities, and adding aesthetic value to the environment. More than just a village landmark, this monument serves as an element that strengthens unity and raises awareness of the importance of preserving local cultural identity. The presence of the Mengkaras Monument is expected to inspire other villages to develop infrastructure that is not only aesthetically valuable but also holds deep social and historical significance for the local community.